2017
DOI: 10.1186/s12888-017-1220-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a clinical practice change intervention in increasing the provision of nicotine dependence treatment in inpatient psychiatric facilities: an implementation trial

Abstract: BackgroundDespite clinical practice guidelines recommending the routine provision of nicotine dependence treatment to smokers in inpatient psychiatric facilities, the prevalence of such treatment provision is low. The aim of this study was to examine the effectiveness of a clinical practice change intervention in increasing clinician recorded provision of nicotine dependence treatment to patients in inpatient psychiatric facilities.MethodsWe undertook an interrupted time series analysis of nicotine dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…At 6‐month follow‐up, the intervention increased documentation of smoking status assessment (36–52% of records), nicotine dependence assessment (5–11%), provision of advice to quit (1–9%), prescription of NRT (8–26%), and treatment of smoking at discharge (9–13%; Wye et al . ). In the second study, Williams et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…At 6‐month follow‐up, the intervention increased documentation of smoking status assessment (36–52% of records), nicotine dependence assessment (5–11%), provision of advice to quit (1–9%), prescription of NRT (8–26%), and treatment of smoking at discharge (9–13%; Wye et al . ). In the second study, Williams et al .…”
Section: Discussionmentioning
confidence: 97%
“…), and a medical record audit ( N = 1054) of psychiatric inpatients discharged between June and October 2009 (Wye et al . ). The patient survey revealed that 31% received brief advice to quit, and while 75% used NRT, only 44% of those patients reported the NRT was sufficient to reduce nicotine withdrawal symptoms (Stockings et al .…”
Section: Introduction/backgroundmentioning
confidence: 97%
See 1 more Smart Citation
“…; Wye et al . , ). Consideration can also be given to piloting community programmes that educate family and carers on how to support quitting. Key messages of these programmes may include reiteration of the importance of supportive language to encourage quitting and information about existing and emerging smoking cessation resources (Patten et al .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although the number of patients who received both teaching and nicotine gum was not statistically significant, there was a marked increase of 20.0%; 0 pre-intervention patients received both, while six post-intervention patients were in this category. Wye, Stockings, Bowman, Oldmeadow, and Wiggers (2017) demonstrated that provision of training, education and feedback to clinical staff resulted in long-term practice changes in terms of tobacco use assessment, provision of advice on cessation and prescribing of NRT to psychiatric inpatients both during admission and at discharge. Their study included a practice change support officer who managed the implementation of project strategies and resources (Wye et al, 2017), suggesting that staff asked to add new tasks to their practice may be most successful with structure and support beyond what we were able to provide.…”
Section: Discussionmentioning
confidence: 99%